(untitled) (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study aims to determine the simultaneous and partial effects of Product Completeness and Word of Mouth on Purchasing Decisions at the KOPMA Perjuangan Insan Madani Kiosk. The research method used in this research is the causality method with a survey approach. The population in this study is not known with certainty. The sampling technique in this study uses accidental sampling with a total sample to be used is 100 people who are consumers of the Insan Madani Struggle KOPMA Kiosk. The type of data used is primary data obtained from questionnaires. The data testing technique used in this study uses validity test, reliability test, and classical assumption test. The results showed that Product Completeness and Word of Mouth simultaneously had an effect on Purchasing Decisions at the KOPMA Perjuangan Insan Madani Kiosk. Product Completeness partially has a significant effect on Purchasing Decisions at the KOPMA Perjuangan Insan Madani Kiosk. Word of Mouth partially has a significant effect on Purchasing Decisions at the KOPMA Perjuangan Insan Madani Kiosk.